Language Planning in Multilingual Nepal: Challenges and Strategies for Preservation and Integration - Lamichhane, Purna Bahadur (Educational Journal, 2024)
This article critically examines language planning in Nepal, emphasizing the systemic marginalization of minority languages in a multilingual setting. It highlights how socio-political and economic pressures compel marginalized communities to adopt Nepali—the dominant language with institutional backing—while their native tongues face functional exclusion from education, administration, and national discourse. Based on a review of existing literature, interviews with educators, and analysis of policy documents, the study reveals how such dynamics contribute to cultural erosion and perceived injustice. It advocates for inclusive, sustainable language planning through multilingual education policies and formal recognition of regional languages as pathways to linguistic equity and preservation. Finally, it proposes potential solutions and recommendations, such as multilingual education policies and the formal recognition of regional languages, to foster linguistic preservation and inclusion in Nepal.